Cyber-Sabotage from The Perspective of Information and Electronic Transactions Regulation - Agung, Dirga; Andi Dewi Pratiwi (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
Most cyber criminals on the internet will be ensnared by Law Number 11 of 2008 concerning Electronic Information and Transactions. The law should offer protection to internet users with good intentions, and provide strict action for cybercrime, especially cyber sabotage actors who disrupt electronic systems and even cause electronic systems to not work properly. Similarly, in Article 5, namely obtaining evidence, there are many obstacles, especially against perpetrators of crimes in Article 33 of Law Number 11 of 2008. Based on the results of the study, it can be concluded that in addition to creating good laws, it also builds the skills of law enforcers to especially find evidence of cybercrime (cybercrime) which is not easy because the crime is in cyberspace by sabotaging the electronic system. In addition, the perpetrators of crimes also hide their identity and the actions they take in cyberspace which is a form of protection.